The Cost of Goods Sold Calculation for Pork Cutting Industry Products in the Darmasaba Village, Abiansemal, Badung - Ni Ketut Sariani; Ketut Sudarmini; Eka Sri Jayanthi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Darmasaba Village in the Abiansemal District, Badung Regency is renowned for its pork-cutting industry, which processes pork into various types of products, ranging from selling raw pork to processed products such as sausages, crackers, red meat, and others. The pricing strategy employed by this pork-cutting industry group, in determining the selling price to consumers, is not yet based on the components that constitute the product; they rely solely on estimation. Therefore, to enhance customer loyalty, it is essential to provide satisfactory service quality through pricing that aligns with product quality, and competitive pricing. To address this situation, the outreach team has undertaken the task of assisting in the formulation of the cost of goods sold for products.